Dominansi Spesies Tumbuhan Lamun di Perairan Pantai Sejuk Kabupaten Lombok Utara - Subagio, Subagio (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Seagrass is a monocotyle plant from the Angiosperms class, which has an important role for marine biota. Seagrass can be said to be a source of life for marine life because it can be a source of food, shelter, and breeding for marine animals. In Pantai Sejuk Waters, North Lombok Regency, there are several species of seagrass that lie along the coast and in shallow sea waters. This study aims to determine the dominance of seagrass in Sejuk Beach Waters, North Lombok Regency. This type of research is a descriptive exploratory research. Sampling using purposive sampling method, by making 3 stations in which there are 3 transects and 4 plots on each transect. Based on the results of the study, 4 species of seagrass were obtained in Sejuk Beach Waters, North Lombok Regency, namely: Cymodocea rotundata as many as 1993 species, Enhalus acoroides with 35 species, Syringodium isoetifolium as many as 2065 species, and Halophila minor as many as 61 species. From the data on the number of species found, it is known that the dominant seagrass with a dominance index value of 0.497 is the Syringodium isoetifolium species. Subsequently, the Cymodocea rotundata species with a dominance index value of 0.479, followed by Halophila minor with a dominance index value of 0.0146, and Enhalus acoroides with a dominance index value of 0.0084.